Spatially and optically tailored 3D printing for highly miniaturized and integrated microfluidics - Jose L. Sanchez Noriega (Nature Portfolio, 2021)
The ever-growing need for highly functional, compact, and integrated microfluidic devices often incurs lengthy and expensive manufacturing processes. Here, authors introduce a generalized 3D printing process that enables fast parallel fabrication of miniaturized, high resolution 3D components.